Isolation and production of polyhydroxybutyrate (PHB) from isolated strain bacillus sp. using crude glycerol as a carbon source - Piwpan, Phakphimol; Jaturapiree, Adisak; Jaturapiree, Phimchanok (Asia-Pacific Journal of Science and Technology, 2016)
Polyhydroxybutyrate (PHB) is polyester produced by a range of microbes under unfavorable growth conditions and stored as an intracellular carbon and energy material. PHB production is more expensive than petrochemical polymer production. The main production cost is the cost of carbon substrate. The aim of this study is to produce PHB using a cheap carbon source, crude glycerol, which is a major byproduct in the biodiesel manufacturing process. PHB producing bacteria species were isolated from the soil collected around biodiesel plants and screened by Nile Red staining method. The effects of sources and concentrations of crude glycerol on the biosynthesis of PHB were investigated. The maximum PHB content obtained after 24 hours of batch cultivation was 23.59 % of cell dry weight at initial crude glycerol of 10 g/L and C:N ratio of 1:0.4.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">